2018
DOI: 10.14419/ijet.v7i3.36.29074
|View full text |Cite
|
Sign up to set email alerts
|

Technical Determinant of Road Accident: A Systematic Review

Abstract: Road accident statistics has been reported increasing over the years and become one of the significant death contributors worldwide. In response towards this issue, appropriate countermeasures need to be outlined. Proposing a preventive plan requires comprehensive understanding on factors behind the occurrence of road accident. Therefore, this review paper aimed at investigating the factors behind the occurrence of road accident focusing on the technical factors. A review over five academic databases such as E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Accordingly, the methodological approach taken in this study is a review of the literature (Dubé & Paré, 2003). Papers from five online databases (Scopus, Web of Science, Emerald, and Google Scholar) were sourced using the keywords: training transfer, transfer of training, employee performance, and job performance (Harith & Mahmud, 2018). The papers were selected based on their relevance to the study objective as well as meeting the criteria of an empirical study.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the methodological approach taken in this study is a review of the literature (Dubé & Paré, 2003). Papers from five online databases (Scopus, Web of Science, Emerald, and Google Scholar) were sourced using the keywords: training transfer, transfer of training, employee performance, and job performance (Harith & Mahmud, 2018). The papers were selected based on their relevance to the study objective as well as meeting the criteria of an empirical study.…”
Section: Methodsmentioning
confidence: 99%
“…Also, RTAs were seen to be some of the main leading causes of death among people under the age of 40 years (Jalilian et al, 2019). It has also been reported that approximately 90% of road fatalities occurred in low and middle-income countries [5].…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, the country has lost 0.8% of its GDP due to road traffic accidents (Shrestha, Bhatta, Shrestha, GC, & Poudel, 2017). There are several technical roads faulty that could in the occurrences of a road accident (Harith & Mahmud, 2018). The weather causes all sorts of wear and tear to road surfaces by wiping away road makings and wearing away the top layer of the road, which helps with the traction of tires (Srinivasa Kumar & Srinivasan, 2013).…”
Section: Introductionmentioning
confidence: 99%